1998
DOI: 10.1518/001872098779649319
|View full text |Cite
|
Sign up to set email alerts
|

Observation versus Hands-on Practice of Complex Skills in Dyadic, Triadic, and Tetradic Training-Teams

Abstract: We saved trainer time and resources by reducing hands-on practice in training-team protocols without reducing computer-based learning. During 1-h sessions, young adults learned Space Fortress, a video task that has been employed during pilot training. Observers (Experiment 1) learned more in 3 sessions than did test-only trainees. Individuals, dyads, triads, and tetrads (Experiment 2) learned in 3 sessions with no differences in learning or interaction between learning and protocol. Individuals, dyads, and tet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 21 publications
3
38
1
Order By: Relevance
“…This interpretation is consistent with previous studies, which have found that when subjects are instructed to visually explore the environment, regardless of interactivity, attention biases are eliminated (Shebilske et al, 1998;. However, the terrain association task was difficult and the data suggests that subjects in neither group (active or passive) performed it well.…”
Section: Interactivitysupporting
confidence: 91%
See 1 more Smart Citation
“…This interpretation is consistent with previous studies, which have found that when subjects are instructed to visually explore the environment, regardless of interactivity, attention biases are eliminated (Shebilske et al, 1998;. However, the terrain association task was difficult and the data suggests that subjects in neither group (active or passive) performed it well.…”
Section: Interactivitysupporting
confidence: 91%
“…In studies in which experimenters emphasize that subjects attend to specific features of the task or environment, no differences are found. For example, Shebilske et al (1998) found no difference between active and passive control in learning flight skills when subjects trained in pairs with one member of the pair controlling the task and the second member of the pair observing as the nature of the social interaction guided the attention of both members of the pair to the critical task features. In tasks of navigation and wayfinding, Wilson, Foreman, Gillett, and Stanton (1997) found no difference between active and passive navigation when they emphasized to passive viewers the importance of attending to the spatial properties of the virtual environment.…”
Section: Mediating Factors: the Role Of Attention Allocationmentioning
confidence: 99%
“…However, they found that the effectiveness of these collaborative tools with computer-based training is moderated by trainees' level of interaction anxiety, with only low-interactionanxiety trainees benefiting from dyadic protocols. In addition, Shebilske et al (1992) reported evidence that collaborative protocols have also been shown to reduce required instructor time and resources by half and found supportive evidence for the social learning theory that observational learning opportunities compensate for hands-on practice efficiently and effectively (Shebilske et al, 1998).…”
Section: E-learningmentioning
confidence: 93%
“…Shebilske et al (1998) demonstrated that students performing a pilot training video task improved their performance from observing another student doing the same task. In addition, students show greater improvement in writing skills after having observed another person thinking aloud while writing, as compared to simply practicing writing on their own (Couzijn 1999).…”
Section: Nadler Thompson and Van Boven Knowledge Creation And Transmentioning
confidence: 99%